KEARIFAN TRADISIONAL DALAM PENGELOLAAN SUMBER DAYA PERIKANAN DI ACEH PADA ERA OTONOMI KHUSUS - Sulaiman, Sulaiman (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Reformation in Indonesia give implication for Aceh, which is the authority in the form of implementation of fisheries management based on traditional wisdom. Those statement above are trying to answer the question of this traditional wisdom in the era of special autonomy. The important finding is critical condition of fisheries resources which is caused by a disregard pattern of traditional management wisdom. It is recommended that policy makers doing holistic approach to fisheries management. Keywords: Fishing, Traditional Wisdom, Aceh